Altered functional connectivity between hypothalamus and limbic system in fibromyalgia. - Kong, Jian.; Huang, Yiting.; Liu, Jiao.; Yu, Siyi.; Ming, Cheng.; Chen, Helen.; Wilson, Georgia.; Harvey, William F.; Li, Wen.; Wang, Chenchen. (Tufts University. Tisch Library., 2021)
Keywords: Resting state functional connectivity, Fibromyalgia, Limbic system, Hypothalamus, Diencephalon, Mind-body intervention.; Springer Open.